Calpains, the proteases of two faces controlling the epithelial homeostasis in mammary gland - García-Trevijano, Elena R.; Ortiz-Zapater, Elena; Gimeno, Amparo; Viña, Juan R.; Zaragozá, Rosa (Frontiers in Cell and Developmental Biology, 2023)
Calpain-1 and calpain-2 are calcium-dependent Cys-proteases ubiquitously expressed in mammalian tissues with a processive, rather than degradative activity. They are crucial for physiological mammary gland homeostasis as well as for breast cancer progression. A growing number of evidences indicate that their pleiotropic functions depend on the cell type, tissue and biological context where they are expressed or dysregulated. This review considers these standpoints to cover the paradoxical role of calpain-1 and -2 in the mammary tissue either, under the physiological conditions of the postlactational mammary gland regression or the pathological context of breast cancer. The role of both calpains will be examined and discussed in both conditions, followed by a brief snapshot on the present and future challenges for calpains, the two-gateway proteases towards tissue homeostasis or tumor development.